Expanding the Notion of Assessment Shell: From Task Development Tool to Instrument for Guiding the Process of Science Assessment Development - Guillermo Solano-Flores; Richard J. Shavelson; Steven A. Schneider (Universidad Autónoma de Baja California, 2001)
We discuss the limitations and possibilities of shells (blueprints with directions for test developers intended to reduce test development costs and time). Although shells cannot be expected to generate statistically exchangeable exercises, they can generate exercises with similar structures and appearances when they are highly specific and test developers are properly trained to use them. Based on our research and experience developing a wide variety of assessments, we discuss the advantages of conceiving shells as: (a) tools for effective development of constructed-response items, (b) formal specifications of the structural properties of items; (c) task-authoring environments that help test developers standardize and simplify user (examinee) interfaces; and (d) conceptual tools that guide the process of assessment development by enabling test developers to work systematically. We also caution against possible misuses of shells.